Endogenous constraints on full productive capacity in a free-market economy - Cole, Nicolas D (Springer, 2023)
The full employment interest rate implicit in classical economic theory is 4½%, deduced by including the rate of normal profit in a simple macroeconomic model. By not fixing the interest rate at this optimum, Central Banks endogenously maintain excess productive capacity, cause unemployment, and encourage the exploitation of Labour by Capital.
Keywords: Full Employment Interest Rate; Productive capacity; Free market